The effects of a one-year swimming course on the swimming skills of police academy students - Dopsaj, M. J.; Milosevic, M.; Blagojevic, M. (Biomechanics and Medicine in Swimming IX, 2003)
This paper aimed to improve the process of assessing the effects of the swimming syllabus within the Department of Special Physical Education (SPE) for the first-year students of the Police Academy, Belgrade, regarding the level and trend of the progress in swimming skills of students (N=51). The test was performed 4 times, at the beginning and the end of each semester of a bisemestral academic year. Each test measured the time at the distances of 25 m, 50 m, 100 m and 200 m swum at maximal intensity. Mathematical modeling was used to calculate the functions representing the ratios of distance-time and velocity-distance, which then yielded the critical velocity (V crit), the rates for the coefficients of energy efficiency (Eetlic), and the coefficients of intensity, capacity and overall power of the energy systems (abpower) required to swim those distances. Statistical analysis was done by MANOV A ( 4x I). The results showed a general trend of progress in students' swimming skills at a statistically significant p = 0.00028 (Wilks' Lambda = 0.171). The changes induced by swimming practice appeared at the VcritlOO and V cn1200, at the Eefficl 00 and Eeffic200 and the abpower2oo at p-level = 0.01. The results suggest a conclusion that it is possible to improve swimming skills in a population of young healthy individuals (noncompetitors) despite a short swimming distance (avg. of300-500 m) and unfavorable frequency of practice (a 45-minute session/week). Another finding was that the level of change that occurred in students' swimming skills follows a definite pattern.